1997
DOI: 10.1007/bf01623682
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of quantitative ultrasound: A review of the relationships with bone mass, osteoporosis and fracture risk

Abstract: Quantitative ultrasound (QUS) is a simple, inexpensive and non-invasive measure of bone which has been used in research settings for the prediction of osteoporosis. This review summarizes the current status of the epidemiology of QUS analysis, including its relationship with bone mineral density (BMD), risk of osteoporotic fracture and risk factors for osteoporosis. Although only moderately correlated with BMD, QUS appears to be as strong a predictor of osteoporotic fracture as BMD and may predict fracture ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
126
1
11

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(143 citation statements)
references
References 79 publications
5
126
1
11
Order By: Relevance
“…These correlation coefficients are on the low end of those reported for other QUS devices. 3,21 A poor correlation between QUS at the calcaneus and axial BMD does not necessarily imply poor diagnostic sensitivity. Large prospective studies as well as cross-sectional studies have shown that QUS at the calcaneus is as good as hip BMD at hip fracture prediction.…”
Section: Correlationsmentioning
confidence: 99%
See 2 more Smart Citations
“…These correlation coefficients are on the low end of those reported for other QUS devices. 3,21 A poor correlation between QUS at the calcaneus and axial BMD does not necessarily imply poor diagnostic sensitivity. Large prospective studies as well as cross-sectional studies have shown that QUS at the calcaneus is as good as hip BMD at hip fracture prediction.…”
Section: Correlationsmentioning
confidence: 99%
“…Large prospective studies as well as cross-sectional studies have shown that QUS at the calcaneus is as good as hip BMD at hip fracture prediction. 3,24,25 The lack of correlation between QUS at the calcaneus and axial BMD has been attributed to many factors: precision and accuracy errors, biological discordance, and different interaction mechanisms. 26 Higher correlations have been observed between QUS and calcaneal BMD (r = 0.66-0.80).…”
Section: Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of bone ultrasonic testers are heel QUS apparatuses [1] measuring the ultrasound velocity and broadband frequency slope of attenuation by through propagation mode in the volume of os calceus dominantly composed of spongeous bone. Axial QUS has a special place among QUS techniques, presenting the advantage of unilateral positioning of the probe in available sites of long bones covered by a thin layer of soft tissues [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…A este respecto, la determinación en el calcáneo podría inducir sesgos al soportar excesiva presión, aunque para algunos autores es la preferente 21 . La exploración con US en las falanges ofrece algunas ventajas 22 : por un lado, son fácilmente accesibles y están constituidas por hueso Nutrición infantil y salud ósea 80.e3 compacto y cortical (el más implicado en la osteoporosis).…”
Section: Article In Pressunclassified